Automatic Trash bin Arduino Project (ATAP) : Enhancing Computational Thinking Skills Through STEM Learning - Lia Laela Sarah (SEAMEO QITEP in Science, 2021)
Computational Thinking is nowadays the fifth of twenty-first-century skills for every individual. Two main approaches to enhance Computational Thinking Skills (CTS) are computer-based and unplug activities. In this study, computer programming exercise was embedded in STEM Learning Using Automatic Trash bin Arduino Project (ATAP). Observations of student’s activities, products, and students’ worksheets were collected and analyzed in accordance with Portfolio assessment rubric consist of some indicator and criteria to get the figuring of student’s computational thinking skills. Based on the data, there are enhancement of Computational Thinking Skills (CTS) during the lesson of ATAP STEM Learning. The CTS was getting better enhancement are abstraction, pattern recognition and decomposition but algorithm design were considered need more time to practice. In addition, the results showed that learning cognitive outcomes with normalized gain <g> valued at 0.66 with average category. These indicates that STEM Learning Using ATAP have positive effect to enhance learning effectivity and Computational Thinking Skills. But there are still need many improvement especially in learning material like module, worksheet and implementation Keywords: ATAP, STEM Learning, Computational Thinking Skill